The Variation of Precipitated Phase Investigated with the Usage of Nonlinear Ultrasonic Technique - Jun YOU; Yunxin WU; Hai GONG (Archives of Acoustics, 2021)
It is well known that nonlinear ultrasound is sensitive to some microstructural characteristics in material. This paper investigates the dependence of the nonlinear ultrasonic characteristic on Al-Cu precipitation in heat-treated 2219-T6 aluminum alloy specimens. The specimens were heat-treated at a constant temperature 155℃ for different exposure times up to 1800 min. The nonlinearity parameter and the changes of precipitates phase were measured for each of the artificially aged specimens. The experimental results show fluctuations in the fractional change in nonlinear parameter (Δβ/β0) and the changes of precipitated phase over the aging time, but with an interesting correlation between the fractional change in nonlinear parameter (Δβ/β0) and the change of precipitate phase over the aging time. Through the experimental data results, the fractional change in nonlinear parameter (Δβ/β0) and the change of precipitate phase over the aging time were fitted curve. Microstructural observations confirmed that those fluctuations are due to the formation and evolution of precipitates that occur in a unique precipitation sequence in this alloy. These results suggest that the nonlinear ultrasonic measurement can be useful for monitoring second phase precipitation in the 2219-T6 aluminum alloy.